Optical Systems and Digital Image Acquisition - Anita Sindar RM Sinaga (Politeknik Ganesha Medan, 2018)
The image is formed continuously and discrete. The color of the image that the human being sees is determined by the color of the light reflected by the object. Visible (visible spectrum) rays that respond to the eye are about 400 nm (blue) to 700 nm (red). The image formed by eyes is a 2D image, while the object being viewed is 3D. The element (row, column) of the matrix represents the average light intensity in the image area represented in pixels. The results of image identification based on the process of color formation and representation into the matrix aims to facilitate the process of image digitization to produce a better image quality. The image generated by the digitalization process is an early stage of processing digital image formation. The information of the object form can be extracted from the result of preprocessing the image. Keyword: RGB, Digital Image, Matrix, Preprocessing